Cutaneous eruptions associated with haematologic malignancies: the need for a unifying nomenclature. (28th February 2019) - Maglie, R.; Grandi, V.; Massi, D.; Caproni, M.; Pimpinelli, N.; Antiga, E.
Abstract : Linked article: L. Visseaux et al. J Eur Acad Dermatol Venereol 2019;33 : e193–e193.https://doi.org/10.1111/jdv.15451